Diagnostic value of metagenomic next-generation sequencing in atypical brucellosis: a case report - Ao, Dungaowa; Li, Xinle; Zhang, Guoliang; Ma, Huiyu; Yang, Lijuan; Tian, Hui; Ao, Shuxia; Feng, Jin; Geng, Wanru (Frontiers in Medicine, 2025)
BackgroundBrucellosis with atypical presentations, such as submandibular abscess without fever, is frequently misdiagnosed.MethodsMetagenomic next-generation sequencing (mNGS) was applied to pus samples from a 47-year-old female with a treatment-refractory submandibular abscess and a history of livestock exposure; results were confirmed serologically.ResultsWithin 48 h, mNGS identified Brucella suis—representing, to our knowledge, the first reported afebrile submandibular infection caused by this pathogen. Targeted therapy with doxycycline and rifamycin led to symptom resolution within 6 days.ConclusionThis case highlights that mNGS, combined with a thorough epidemiological history, can resolve diagnostic dilemmas in atypical brucellosis, guide precise treatment, and mitigate antibiotic misuse.